Whereas an observer has nothing to do with it! - Ashursky, Emir E.
In this article, the author, as possible, subjects to a comprehensive (though mostly, it's true, critical) analysis the one-sided attempts of a number of current Western astrophysicists to somehow substantiate the well-known Fermi paradox. Is it a joke to say: in own perverted designs, some of them even go so far as to unceremoniously rearrange the cause with the effect! However, so to speak, "for greater pluralism of views", we'll along the way quote many other, much clearer and sapider opinions on this topic-right from the lips of alternatively thinking scholars (and besides - I note - with a world name!). Wherein some of them frankly assess the today stalemate uncertainty as a kind of creative stagnation; second are inclined towards the version of consumerity-driven global theoretical shift; while third directly declare that it is time for representatives of the exact sciences, obviously, to prepare for the change of the old starry paradigm to cardinally updated one. But still, without waiting for the weather by the sea (as well as just for spite the arrogant purse-proud Yankees, who, alas, do not seriously recognize our current potential capabilities, or even past truly grandiose achievements), here we will try independently to resolve some of the most controversial issues.
Keywords: Astronomy